2008
DOI: 10.1017/s0022215108002004
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for patients referred urgently with suspected head and neck cancer

Abstract: In a group of patients with symptoms suggestive of head and neck malignancy, only 12 per cent were ultimately diagnosed with cancer. Of all the patients within the trust diagnosed with head and neck cancer, 44 per cent had come from outside the urgent referral pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…This study also audited all head and neck cancer diagnoses made over the same period showing that 71% of these patients were not referred via the fast-track system. Similar studies by Williams et al [9] and Hobson et al [10] showed a cancer diagnosis in 11 and 12% respectively, of patients referred via a fast-track system over an annual period. However, similar to our study, of the 12% of cancer diagnoses made by Hobson et al, only 5% were primary head and neck cancer, the remainder being lymphoma and a variety of other malignancies.…”
Section: Discussionsupporting
confidence: 69%
“…This study also audited all head and neck cancer diagnoses made over the same period showing that 71% of these patients were not referred via the fast-track system. Similar studies by Williams et al [9] and Hobson et al [10] showed a cancer diagnosis in 11 and 12% respectively, of patients referred via a fast-track system over an annual period. However, similar to our study, of the 12% of cancer diagnoses made by Hobson et al, only 5% were primary head and neck cancer, the remainder being lymphoma and a variety of other malignancies.…”
Section: Discussionsupporting
confidence: 69%
“…7,9,10 Three studies 5,6,8 did not report the data regarding the compliance of the referrals to the NICE guidelines and were therefore not included in the analysis.The positive predictive values of each of the referral criteria were only outlined in the paper by McKie et al 10 and so collective data were not available for meta-analysis.…”
Section: -10mentioning
confidence: 99%
“…5 Hobson et al demonstrated that referrals marked as urgent, which were proofread by a consultant, had a mean waiting time of 15.5 days. 9 Although there is no evidence to suggest that these delays are secondary to the greater workload generated by fast-track referrals, the increased workload to meet 2ww targets must be considered. In the setting of breast cancer, a much more common entity where the numbers of referrals are higher, there is clear evidence that the 2ww rule has led to increased waiting times for routine appointments.…”
mentioning
confidence: 99%
“…Most importantly, these studies have shown that only 5.6%‐14.6% of 2‐week referrals were diagnosed with a head and neck cancer and that majority of the cancer diagnoses were in fact via other referral routes …”
Section: Introductionmentioning
confidence: 99%